FINANCIAL ANALYSIS OF BROILER BREEDING BUSINESS FED WITH AZOLLA JUICE THROUGH DRINKING WATER - I K. A., Pradnyana; Putri, B. R. T.; Siti, N. W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the business income of broilers given azolla juice in drinking water. This research was conducted for six weeks in Banjar Metra Kelod, Yangapi Village, Tembuku District, Bangli Regency. The design used was a complete randomized design (CRD) consisting of 4 treatments and 4 replicates with a total of 64 chickens used. The treatments given were without the addition of azolla juice to drinking water (P0), the addition of 2% azolla juice (P1), the addition of 4% azolla juice (P2), and the addition of 6% azolla juice (P3). The observed variables include income analysis based on cost, revenue, income, 365 R/C ratio and BEP. The results of the income analysis showed that chickens with 4% azolla juice gave the best results with an income of Rp 117,523,-/per period of live weight with an R/C ratio of 1.223. BEP production unit of 20.55 kg live weight, BEP selling price of chicken per kg Rp 23,000/kg live weight, and BEP revenue of Rp 273,819/per period. Based on the results of the study it can be concluded that the addition of azolla juice to drinking water can increase the income of broiler breeds.